1998
DOI: 10.1038/sj.ejcn.1600624
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein profiles and serum peroxide levels of aged women consuming palmolein or oleic acid-rich sunflower oil diets

Abstract: Objective: To investigate the hypercholesterolemic effects of a dietary exchange between 16:0 and 18:1 while 18:2 was at relatively lower level ( % 4%) in aged women with initially high total serum cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) values and with high intakes of dietary cholesterol. Design: Subjects were assigned to two consecutive 28 d periods. In the ®rst period all subjects followed an oleic acid-rich diet in the form of oleic acid-rich sun¯ower oil. This was followed by a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
(32 reference statements)
1
16
0
2
Order By: Relevance
“…Present results are relevant as it has been found that lipoprotein profiles at birth and at age 4 are associated [10]. Diets enriched in SFA have been found to increase LDL-c and Apo B values [45] by decreasing the number and activity of LDL-R [44], although information relating maternal diets with LDL-R activity/number during the fetal period is scarce. The higher LDL-c values at the low-MDA-score group show some relationship with a nonsignificant tendency for higher (33 %) oxLDL while AE did not significantly change.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Present results are relevant as it has been found that lipoprotein profiles at birth and at age 4 are associated [10]. Diets enriched in SFA have been found to increase LDL-c and Apo B values [45] by decreasing the number and activity of LDL-R [44], although information relating maternal diets with LDL-R activity/number during the fetal period is scarce. The higher LDL-c values at the low-MDA-score group show some relationship with a nonsignificant tendency for higher (33 %) oxLDL while AE did not significantly change.…”
Section: Discussionmentioning
confidence: 72%
“…The existence of active LDL receptors (LDL-R) controlling circulating LDL particles has been reported in the fetus [43]. As each LDL particle contains just a molecule of Apo B [44], it can be calculated that neonates whose mothers consumed high-MDA-score diets presented 43 % less LDL particles than their MDA <7 counterparts. Present results are relevant as it has been found that lipoprotein profiles at birth and at age 4 are associated [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some workers observed increase (Cuesta et al 1998;Mutalib et al, 1999;Mutalib et al, 2002), others report decrease (Zhang et al, 1997a;Zhang et al, 1997b), and yet others no effect (Bosch et. al.…”
Section: Discussionmentioning
confidence: 99%
“…The initial increase in LDL level in the 8 th week declined to a significantly lower level than the control at the 12 th week in this study, a finding that agrees with other workers (Kamisah et al, 2005;Karaji-Bani et al, 2006). However, other reports of increase in LDL had been made (Cuesta et al, 1998;Mutalib et al, 1999;Mutalib et al, 2002). Increased level of LDL had been documented to contribute to hyperlipidaemia, progression of atherosclerosis and cardiovascular disease (Lawn, 1992;Nwanjo and Oze, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation